Monetary Policy, Heterogeneous Expectations, and the Return of High Inflation - Fabio Milani (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper studies the transition to high inflation during the COVID-19 pandemic, using a behavioral version of the New Keynesian model, which replaces the conventional assumption of Rational Expectations with subjective and heterogeneous expectations. Different shares of agents in the economy form expectations based on alternative views regarding future economic variables: 1) a share of agents forecasts that inflation and output will rapidly revert to steady state; 2) another share forms forecasts based on a model resembling the MSV solution under rational expectations; 3) a third share of agents uses an under-specified model that captures trend-following, adaptive, or extrapolative behavior. Agents learn over time the parameters of their perceived model and they can also shift across different views based on past forecasting performance. The macroeconomic model is estimated using Bayesian methods to fit realized macroeconomic variables and data on expectations from surveys. The results document an additional channel that operates through switches in agents' perceptions and amplifies the impact of the original inflationary shocks. In response to rising inflation after COVID, agents begin shifting from the mean reversion model to the trend-following specification (with a belief about perceived inflation persistence that is simultaneously revised upward). Consequently, the impact of inflationary shocks is magnified and the effects of monetary policy attenuated.
Keywords: E31; E32; E52; E58; E65; E70; 330; heterogeneous expectations; post-COVID inflation; learning; inflation persistence; monetary policy effectiveness